REIMAGINING MALACCA’S HERITAGE SHOPHOUSES: ADAPTATIONS FOR TOURISM SUPPORTING FACILITIES - Paramitha, Ida Ayu Shanty Pradnya; Susanti, Ardina; Mahira, Eka Diana (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Malacca City, a UNESCO World Heritage Site since 2008, represents a rich tapestry of multicultural and colonial history. The city’s heritage shophouses, exemplifying architectural styles influenced by Portuguese, Dutch, British, and Chinese traditions, play a vital role in preserving its identity. This study explores the adaptive reuse of these shophouses, focusing on their transformation into tourism-supporting facilities such as homestays and cafés. Case studies of Ohana House, a boutique homestay, and Ban Kheng Café highlight how minimal intervention and architectural harmony maintain historical integrity while accommodating contemporary tourism needs. The findings emphasize the balance between preservation and modernization, achieved through minimal alterations, strategic reuse of spaces, and maintaining visual compatibility. Challenges such as utility limitations and sustainability issues persist, underscoring the need for innovative solutions to enhance both operational efficiency and visitor experience. Recommendations include integrating sustainable technologies and expanding cultural offerings to enrich the heritage tourism experience while safeguarding Malacca’s unique identity. Overall, this research demonstrates the potential of heritage conservation to contribute to sustainable urban development, cultural preservation, and economic growth in historic settings like Malacca.